Tuberculosis treatment outcome in an antiretroviral treatment programme at Lebowakgomo Hospital, Limpopo Province - Monepya, Refilwe Gift (My University, 2022)
Background: Tuberculosis(TB) and Human Immunodeficiency virus(HIV) continues to be a public health concern globally. There is no data on TB outcomes on HIV programme outcome in Lebowakgomo hospital of Limpopo Province. The main objective of this study was to determine the TB treatment outcomes in TB/HIV co-infected people at Lebowakgomo hospital in Limpopo Province. Methodology: A quantitative retrospective design was used in the study in which a sample size of 180 patients’s files who are 18 years and above and TB/HIV co-infected were reviewed. A self-designed data collection tool was used to collect data. The tool covered variables such as age, gender, HIV status, CD4 cell count, type TB, duration on TB treatment and the outcome. Data was analysed using the STATA statistical software version 12 for Windows (STATA Corporation, College Station, Texas). Results: The majority of records were age group 35-44 years at 32%. There was a statistical significance differences (p˂0.001) between males and females in relation to age groups. TB treatment success rate was 68.9% and mortality 16.9%. Females were more likely to complete TB treatment successfully than males. Overall age, gender, previous TB infections, TB type, duration on ART and CD4 Count were not significantly associated with treatment outcomes amongst TB/HIV co-infected people. Conclusion: This study has revealed that TB treatment success rate in HIV co-infected is lower (68.3%) than the WHO target of 85%.
Thesis (MPH.) -- University of Limpopo, 2022
Keywords: Tuberculosis; Antiretroviral programme; Tuberculosis treatment outcome; Mycobacterium tuberculosis; Tuberculosis; Antiretroviral agents; HIV-positive persons -- South Africa -- Limpopo; Tuberculosis -- Treatment